AJARAN BHAKTI MARGA SEBAGAI LANDASAN MENUMBUHKEMBANGKAN KARAKTER SISWA - Pradna Lagatama; Nyoman Dane (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Law Number 20 of 2003 concerning the National Education System has emphasized that the goal of national education must be pursued to be achieved by all education providers in Indonesia. To achieve this, a special analysis is needed at the education level, adapted to the level of ability and needs of students. Formally, school is a place to study religion and a place to guide students.Education has meaning and an important role in life. Educational institutions are expected to take over the roles and responsibilities of families in shaping the character of students. In shaping students' morals and character, the application of morals and ethics is the basic point that must be realized by an educator. Learning is not only understood in theory but is applied in the behavior of each student's life so that it can show the character of students leading to a better direction. In this case, what is appropriate to be applied to overcome the problem of moral degradation is the teachings of Bhakti Marga so that it can shape the morals, ethics and habits of students towards male students. The forms of Bhakti Marga teachings in developing students' character are: carrying out prayers, preserving the environment, maintaining the cleanliness of holy places. Regarding the impact of Bhakti Marga teachings in developing student character, it is to increase students' religious attitudes, create student discipline, form tolerance in students, increase environmental care, and increase students' sense of responsibility. So that the teachings of Bhakti Marga can be used as guidelines in daily life in order to maintain a harmonious balance of the natural environment. Keywords: Bhakti Marga Teachings, Student Character